2018
DOI: 10.1108/mf-05-2017-0192
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the moderating effect of Shariah Board on the relationship between financial performance and accounting disclosure

Abstract: Purpose Shariah Board (SB) is considered as a typical corporate governance mechanism for the Islamic banking system. This board takes the responsibilities of assuring the compliance of transactions and operations with Islamic rules and principles. The purpose of this paper is to measure the SB quality and examine its moderating effect on the relationship between financial performance and accounting disclosure quality. Design/methodology/approach This study used a sample of 90 Islamic banks (IBs) during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…Four firm level control variables namely EQTA, NLTA, log of total assets (LnTA) and Z-score were used for the empirical investigation.ICG index was found consistently insignificant in all of the 6 models results, this does not supports hypothesis H1. This finding is consistent with the work of (Ajili & Bouri, 2018). SBS is found positively significant for all the three performance variables.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Four firm level control variables namely EQTA, NLTA, log of total assets (LnTA) and Z-score were used for the empirical investigation.ICG index was found consistently insignificant in all of the 6 models results, this does not supports hypothesis H1. This finding is consistent with the work of (Ajili & Bouri, 2018). SBS is found positively significant for all the three performance variables.…”
Section: Resultssupporting
confidence: 92%
“…Erol, F, Aydogan, and Tunç (2014) found that IBs in Turkey are more profitable than CBs. Ajili and Bouri (2018) assert that IBs in GCC countries valued the effectiveness of SSBs much more than the CBs governance mechanisms. Indeed, a reasonable consensus in the literature suggesting that IBs improve firms profitability, however, research on Shari' ah supervisions in relation to firms performance is still low, particularly Shari, ah governance on the IBs performance (Nathan, 2010;Mollah & Zaman, 2015).…”
Section: Literature Review and Formulation Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation results for Model 1 indicate that SIZE is significantly positively associated with the level of compliance (coef =0.069; p =.0047). This finding is aligned with previous literature that suggests that larger firms are expected to disclose more information than smaller firms (Ajili & Bouri, 2018;Archambault & Archambault, 2003;Cascino & Gassen, 2015;Mazzi et al, 2018;Santos et al, 2014).…”
Section: Determinants Of Level Of Compliancesupporting
confidence: 92%
“…Similarly, firm size is positively associated with the level of disclosure (Ajili & Bouri, 2018;Cascino & Gassen, 2015;Mazzi et al, 2018;Santos et al, 2014). Larger firms tend to be more exposed to public demand for information and are therefore more likely to disclose more to reduce political pressure (Archambault & Archambault, 2003).…”
Section: Explanatory Factors and Empirical Modelsmentioning
confidence: 99%